A Virtual Reality Game (The Secret Trail of Moon) for Treating Attention-Deficit/Hyperactivity Disorder: Development and Usability Study - Maria Rodrigo-Yanguas; Marina Martin-Moratinos; Angela Menendez-Garcia; Carlos Gonzalez-Tardon; Ana Royuela; Hilario Blasco-Fontecilla (JMIR Publications, 2021)
BackgroundAttention-deficit/hyperactivity disorder (ADHD) affects between 4% and 8% of children worldwide. The treatment of choice is multimodal treatment. Multimodal interventions for ADHD may be improved by incorporating new treatments, such as treatment via serious video games. The Secret Trail of Moon (TSTM) is a virtual reality serious video game that was designed for cognitive training related to core ADHD symptoms and executive dysfunction. ObjectiveWe aimed to describe the development and usability of TSTM. MethodsThe usability study included 37 children and adolescents who tested TSTM during the early usability stage (preinclusion) of a randomized controlled clinical trial for testing the effectiveness of TSTM. Chi-square tests were performed to compare patients with ADHD (ADHD combined subtype vs inattentive subtype) and to compare frequent and infrequent video game players in the second study. We used SPSS version 20 for Macintosh (IBM Corporation). ResultsA total of 31/37 (86%) and 30/37 (83%) of participants liked playing TSTM and wanted to continue playing TSTM, respectively. Further, 5/37 (14%) of participants reported that they experienced either perceived dizziness or virtual reality motion sickness. We found no statistically significant differences after comparing the ADHD combined subtype to the inattentive subtype and frequent video game players to infrequent video game players. ConclusionsSerious video games, such as TSTM, may complement the current multimodal approach for treating ADHD. Trial RegistrationClinicalTrials.gov NCT04355065; https://clinicaltrials.gov/ct2/show/NCT04355065